Renewable Energy Conversion with hybrid Solar Cell and Fuel Cell - Aris Ansori; Indra Herlamba Siregar; Subuh Isnur Haryuda (UPT Penerbitan Universitas Jember, 2016)
The greater the electrical energy consumption by growth in industrial and residential areas. Potential for solar energy 4.5 KW/m2/day can be converted into electrical energy with a solar cell, biofuel energy can be converted into electrical energy with a fuel cell. solar cell and fuel cell can be used for power generation hybrid renewable energy. Research experiment with designing hybrid renewable energy power plants. Research variable; a) the independent variable; variation of the load ,10 watt, 15 watt, 25 watt, 35 watt, 40 watt; b). The dependent variable: the performance of renewable energy power plants; c) Control variables: capacity 200Wp solar cell and fuel cell 12 watt. The results of the research performance of renewable energy power plants to the electrical energy produced by solar cell range 146,80 - 168,92 watt. Average per day to produce electricity of 168.92 watts x 6 hours of irradiation = 1013.54 Wh. While the fuel cell average of 9.43 watts used to supply electrical energy when the solar cell does not produce electricity. The electrical energy stored in the battery can be turned 125 watt load for 8 hours.